EFEK INTERVENSI PENDIDIKAN BERBASIS SEKOLAH TERHADAP TINGKAT PENGETAHUAN TENTANG PENCEHAGAN KEGEMUKAN DI ANTARA ANAK-ANAK USIA 9-10 TAHUN Di KOTA BANDUNG - Hermina, Hermina; Afriansyah, Nurfi; Jahari, Abbas B. (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
Effect of School-Based Educational Interventions On The Level of Obesity Prevention's Knowledge Among 9-10 Year-Old Children In Bandung City. Background: The prevalence of obesity in Indonesia shows an increasing trend. A survey among adults in 12 major cities in Indonesia shows the prevalence of obesity in adult is more then 20%. The prevalence among school age children is 6.0%. Obesity in childhood is known to be an independent risk factor for adult obesity. Objectives: To assess the effect of school-based educational intervention on the level of obesity prevention's knowledge, among elementary school-aged children. Methods: This study having non-control group pre- and post-test design was based in three Bandung's Elementary Schools in 112 children aged 9 to 10 years. The three schools were selected from six Bandung's Elementary Schools having both high socio-economic status and more obese children based on the Office of Basic Education. The intervention schools drawn from SDN M5 included 39 children gave the Obesity Prevention's booklet by their teacher for their parent (Group A), SD P1 36 children gave the booklet for themselves (Group B), and SD P2 37 children gave the booklet for their parent and themselves (Group C). All children were measured their weight and height and were interviewed using structured questionnaire that covered their characteristics and the five topics about obesity (definition, causes, consequences, how to identify, and how to weight control). Data were analyzed descriptively and tested by Chi-square and t-tests. Results: At baseline, most of children (>90%) had less of knowledge in the obesity prevention. After intervention, only the Group B & C had significantly increase in the knowledge (p<0.05). However, between the two groups, the Group C was more effective in increasing the knowledge. Conclusion: Educational intervention giving the Obesity Prevention's booklet by teacher to school children and their parents was more effective in increasing the knowledge of obesity prevention's. Keywords: obesity prevention, school-aged children, school-based, educational-intervention, parent.